Efficacy and safety of lubiprostone combined with polyethylene glycol electrolyte powder for bowel preparation in patients classified by risk level: a randomised trial - Song, Jian; Li, Hong-Liang; Qi, Xu-Fei; Chen, Chang-Xi; Xu, Yue-Mei (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to assess the efficacy and safety of lubiprostone combined with polyethylene glycol (PEG) electrolyte powder for bowel preparation in patients classified by risk level.MethodsThe following factors were considered to be associated with inadequate bowel preparation: constipation (meeting Rome IV criteria), BMI > 25 kg/m², history of inadequate bowel preparation, colorectal surgery, diabetes, stroke, or spinal cord injury, Parkinson’s disease, and use of tricyclic antidepressants or anesthetics. A total of 424 patients scheduled for colonoscopy were included and categorized into high-risk and low-risk groups based on bowel preparation risk factors. These patients were then randomly assigned to block groups. The high-risk group was further subdivided into the H-PEG subgroup (PEG, 99 cases) and the H-PEG+L subgroup (PEG + lubiprostone, 105 cases), while the low-risk group was divided into the L-PEG subgroup (PEG, 103 cases) and the L-PEG+L subgroup (PEG + lubiprostone, 102 cases). The following parameters were assessed in each group: time to first bowel movement, total bowel movement count, adverse reactions during preparation, insertion and withdrawal durations, Boston Bowel Preparation Scale (BBPS) scores, rate of adequate bowel preparation, colorectal adenoma detection rates, and willingness to undergo repeated bowel preparation.ResultsDuring bowel preparation, the H-PEG+L subgroup exhibited a shorter time to first bowel movement and a higher total bowel movement count than the H-PEG subgroup (p < 0.05). Similarly, the L-PEG+L subgroup demonstrated a reduced time to first bowel movement and increased total bowel movements compared to the L-PEG subgroup (p < 0.05). Within the high-risk group, the H-PEG+L subgroup had higher BBPS scores, a higher rate of adequate bowel preparation (p < 0.05), and greater willingness to undergo repeated bowel preparation (p < 0.05). No significant differences were found in the low-risk group. Additionally, no differences were observed between groups regarding adverse reactions, insertion duration, withdrawal duration, or adenoma detection rates.ConclusionAmong patients classified as high risk for inadequate bowel preparation, the combination of lubiprostone and PEG electrolyte powder significantly enhances BBPS scores and bowel cleanliness compared to PEG electrolyte powder alone, without increasing the incidence of adverse events, and is more acceptable for repeated bowel preparation. However, in patients classified as low-risk, the addition of lubiprostone does not provides additional benefits.Clinical trial registrationhttps://clinicaltrials.gov, identifier ChiCTR2400088155.